Eliciting health beliefs: Difficulties and solutions - Xiaoxue Sherry Gao; Rong Rong (PLoS ONE, 2026)
Despite recent progress in the development of incentive-compatible belief elicitation methods, some unique challenges arise when researchers apply some methods to elicit one’s beliefs about their own health status. First, the unavailability or unverifiability of one’s own health outcomes to incentivize the elicitation procedure. Second, the opportunity to hedge against adverse health outcomes by increasing the associated monetary payoffs in an incentivized elicitation task. To solve these issues, we elicit participants’ beliefs about their close peers as proxies for their beliefs about themselves. We first collected the health outcomes of others with similar health status using a pre-experiment survey. Then, we used the surveyed outcomes to incentivize the belief elicitation procedure in the laboratory experiment stage. We conclude that the elicited beliefs are reflective of their beliefs about their own health status because the elicited beliefs using our proposed method are highly correlated with the participants’ own past health outcomes.